Bacterial diseases of bananas and enset: current state of knowledge and integrated approaches toward sustainable management - Blomme, Guy; Dita, M.; Pérez Vicente, L.; Molina, A.; Ocimati, W.; Poussier, S.; Prior, P.; Jacobsen, K.S. (Frontiers Media, 2017)
Bacterial diseases of bananas and enset have not received, until recently, an equal amount of attention compared to other major threats to banana production such as the fungal diseases black leaf streak (Mycosphaerella fijiensis) and Fusarium wilt (Fusarium oxysporum f. sp. cubense). However, bacteria cause significant impacts on bananas globally and management practices are not always well known or adopted by farmers. Bacterial diseases in bananas and enset can be divided into three groups: (1) Ralstonia-associated diseases (Moko/Bugtok disease caused by Ralstonia solanacearum and banana blood disease caused by R. syzygii subsp. celebesensis); (2) Xanthomonas wilt of banana and enset, caused by Xanthomonas campestris pv. musacearum and (3) Erwinia-associated diseases (bacterial head rot or tip-over disease Erwinia carotovora ssp. carotovora and E. chrysanthemi), bacterial rhizome and pseudostem wet rot (Dickeya paradisiaca formerly E. chrysanthemi pv. paradisiaca). Other bacterial diseases of less widespread importance include: bacterial wilt of abaca, Javanese vascular wilt and bacterial fingertip rot (probably caused by Ralstonia spp., unconfirmed). This review describes global distribution, symptoms, pathogenic diversity, epidemiology and the state of the art for sustainable disease management of the major bacterial wilts currently affecting banana and enset.